Simulating the Impact of Fuel Prices Rising and Direct Cash Assistance Compensation (BLT BBM) on Poverty in Indonesia - Ariful Romadhon; Ardi Adji (Jurnal Ekonomi dan Studi Pembangunan, 2024)
Crude oil prices have become volatile as geopolitical conflicts that occur in oil-exporting countries make the Indonesian government have to increase fuel prices and plan to provide cash transfers as compensation. This study analyzes the impact of fuel price rising and the direct cash assistance compensation program/Bantuan Langsung Tunai (BLT BBM) on poverty using micro data simulation. Poverty simulation is generated by modifying the poverty line (GK) and expenditure by utilizing leading indicators such as commodities inflation, household consumption expenditure growth, and population growth. The simulation results show that the presence of compensation can reduce the poverty rate compared to the absence of compensation. Without compensation, the poverty rate in September 2022 is predicted to be 10.36 percent (0.82 percent higher than in March 2022), while under the government's scheme where compensation is given to households receiving the Family Hope Program (PKH)/Non-Cash Food Assistance (BPNT), poverty is predicted to be 9.56 percent (0.02 percent higher than in March 2022). Exclusion error in the program of 55.35 percent in the lowest decile is an obstacle in poverty alleviation. Improvement and updating of the database of program recipients is needed so that the program can be more targeted to reach the poor.